(untitled) (University of Khartoum Engineering Journal, 2022)
As the interconnected power system transmits power from one area to another, the frequency will inevitable deviate from scheduled frequency. In addition, the active and reactive power demands continually change with rising and falling trend. Any mismatch between system generation and demand results in change in system frequency that is highly undesired. Excitation of generator must be regulated in order to match the power demand, otherwise the bus voltage may fall beyond the permitted limit. In this paper, a simulation model is developed for each component of AGC and AVR loops considering generator rate constraints. The response with GRC is compared with the analysis done without the Generation Rate Constraint. Although the frequency deviation is less with suitable controllers when the GRC is not considered, it is not the actual frequency deviation. When GRC is considered the actual frequency deviation can be found and then accordingly the controller is tuned. So that the desired frequency and power interchange with neighboring systems are maintained in order to minimize the transient deviations and to provide zero steady state error in appropriate short time. Further the role of automatic voltage control is to maintain the terminal voltage of synchronous generator in order to maintain the bus bar voltage Results are obtained using MATLAB SIMULINK software.